Knowledge of Children Sex Education Ages 5-6 Years Reviewed from The Implementation of Protect Our Selves Media - Nofiana, Nia; Tasuah, Neneng (Jurusan PGPAUD FIP UNNES, 2020)
Cases of adult sex abuse against children are rampant, indicating that sex education from an early age is very important. Adults consider children as innocent beings, so they are often targeted by sex. Child innocence is also used by individuals to carry out immoral acts against children. The problem statement from this study is whether there is a difference in knowledge about early childhood sex education before and after the application of the Protect Our Selves media in learning, and whether the mean score after being given the application of the Protect Our Selves media in learning is knowledgeable about sex education is higher than the child before applying the Protect Our Selves media. The aim is to obtain facts and explain the differences in knowledge of child sex education before and after using the Protect Our Selves media and to explain that children who learn to use the Protect Our Selves media have higher knowledge about early childhood sex education than children before using the Protect Our Selves media. This research is a kind of quantitative research with the research subjects being children aged 5-6 years at Pertiwi Gambuhan Kindergarten Pulosari District, Pemalang Regency, with 31 children. Methods of data collection in the form of observation, Likert scale, documentation. Technical data analysis using descriptive analysis. The results of the study based on statistical calculations, obtained t_count = 10.36212 from the distribution list t with t_table = 2.042. So that it can be concluded that ã€–tã€— count> t_table then H_0 is rejected and H_1 is accepted. So there is a significant difference between the knowledge of sex education in children before and after the application of learning through the media Protect Our Selves. Based on the descriptive analysis on the results of the calculations that have been done, the mean is 157.74 at the pretest value, and the mean is 201.65 at the posttest value. This means that the second hypothesis is accepted, that is, the child after being applied to the Protect Our Selves media has a higher knowledge of sex education than the child before applying the Protect Our Selves media.